One-component sealant and preparation method thereof

By adding tris(triphenylphosphine) copper fluoride to the sealant formula, the crosslinking reaction is promoted to form a three-dimensional network structure, the problem of poor performance of sealant under high temperature and ultraviolet irradiation is solved, and the high temperature and ultraviolet irradiation resistance of sealant is improved.

CN118562441BActive Publication Date: 2025-05-02GUANGZHOU XINYUE NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410674309.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2025-05-02
Estimated Expiration
2044-05-28

AI Technical Summary

Technical Problem

Existing sealants have poor performance under high temperature and ultraviolet irradiation, making it difficult to meet the needs of automotive glass sealing.

Method used

A single-component sealant formula is adopted, including α,ω-dihydroxypolysiloxane, hydrophobic vapor-phase white carbon black, nano-calcium carbonate, silicon micropowder, carbon black, water removal agent and other components, and the crosslinking reaction is promoted to form a three-dimensional network structure by adding tris(triphenylphosphine) copper fluoride and other organic metal compounds.

Benefits of technology

The sealant has improved its high temperature and ultraviolet radiation resistance, enhanced its initial shear strength, and after long-term exposure to salt spray, ultraviolet rays and high and low temperature conditions, the shear strength attenuation rate is no more than 7%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004863584860000031
    Figure BDA0004863584860000031
  • Figure BDA0004863584860000032
    Figure BDA0004863584860000032
  • Figure BDA0004863584860000061
    Figure BDA0004863584860000061
Patent Text Reader

Abstract

The present application belongs to the technical field of sealant preparation, and discloses a one-component sealant, which comprises, by mass, 40-50 parts of α, ω-dihydroxy polysiloxane, 5-10 parts of hydrophobic fumed silica, 40-50 parts of nano calcium carbonate, 5-10 parts of silicon micropowder, 0.5-1 parts of carbon black, 1-2 parts of a dehydrating agent, 6-13 parts of a cross-linking agent, 0.01-0.1 parts of a catalyst, and 1-8 parts of an organic metal compound, wherein the organic metal compound is selected from at least one of tri(triphenylphosphine) copper fluoride, tri(triphenylphosphine) copper chloride, tri(triphenylphosphine) copper bromide, bis(triphenylphosphine) nickel difluoride, bis(triphenylphosphine) nickel dichloride, and bis(triphenylphosphine) nickel dibromide. The present application obtains a one-component sealant with good heat resistance and UV resistance through the above design. In addition, the present application also discloses a preparation method of the one-component sealant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sealant preparation, and in particular to a single-component sealant and a preparation method thereof. Background Art

[0002] As a vital connection and sealing material in automobile manufacturing, the technical background of automotive glass sealant covers multiple fields such as materials science, chemical engineering, and mechanical engineering. With the continuous progress of the automobile industry, the performance requirements for sealants are also constantly improving, which has promoted the continuous innovation and development of sealant technology. Automotive glass sealants are usually based on polymer materials such as polyurethane, silicone or polysulfide, and their chemical composition is complex, including base polymers, cross-linking agents, catalysts, fillers, plasticizers, stabilizers and other ingredients. The precise proportion and selection of these ingredients play a decisive role in the performance of the sealant. At the same time, the performance requirements of special sealants for automotive glass are extremely strict. The sealant must be able to form a strong bond with materials such as automotive glass and car body metal to ensure that no peeling occurs under various environmental conditions. This is crucial to the safety of the car. At the same time, since the car is driving outdoors, the sealant must be able to resist the influence of harsh environments such as ultraviolet rays, ozone, extreme temperatures, and maintain long-term stability. This is crucial to the durability of the car. After being subjected to external forces, the sealant should be able to quickly return to its original state and maintain the sealing effect. This is crucial to the comfort and sealing of the car. In addition, the car may be exposed to various chemicals during operation, such as fuel, lubricating oil, cleaning agents, etc. The sealant must be able to resist the erosion of these substances, which is crucial to the reliability of the car. In addition, for ease of operation, the sealant should be easy to extrude, have a moderate curing speed, and be able to complete the operation within the specified construction time, which is crucial to the efficiency of automobile production.

[0003] Chinese patent application 202111474575.3 discloses a high temperature resistant sealant and its preparation method and application. The high temperature resistant sealant includes the following raw material components in parts by weight: 20 to 50 parts of modified silane; 5 to 20 parts of reinforcing agent; 5 to 10 parts of curing agent; 5 to 15 parts of film-forming agent; 10 to 70 parts of inorganic filler; the modified silane is a carboxylate.

[0004] The metal ions on the organic carboxylate groups of the sealant of this scheme participate in the phase transformation of the system at high temperature, promote the vitrification and ceramicization of the system, and finally transform the sealant into a ceramic sealant, which has the characteristics of radiation resistance, acid and alkali resistance, moisture resistance, and no cracking. The sealant still has good electrical insulation performance under high temperature, irradiation and humidity conditions, and can work for a long time in harsh environments such as nuclear reactors and blast furnaces;

[0005] Further observation of the document shows that although metal oxides or metal hydroxides containing metal elements are also used in this scheme, its purpose is to react between metal oxides or metal hydroxides containing metal elements and carboxylic acid, and then use the reaction product to modify polysiloxane, and then use modified polysiloxane and modified polysilazane to prepare modified silane. It can be seen that the design of this scheme is more centered on the modification of silane as the basic component of the sealant. At the same time, the scheme further explains in paragraph 14 of the specification that the working principle of modified silane is: the metal ions on the organic carboxylate group participate in the phase transition of the system at high temperature, promote the vitrification and ceramicization of the system, and finally form a dense ceramic sealant.

[0006] Chinese patent application 202111247024.3 discloses a silicone sealant for a U-shaped heating tube and a preparation method thereof, which includes the following components by mass ratio: 100-150 parts of α, ω-dihydroxy polysiloxane, 10-20 parts of ketoxime crosslinking agent, 0-100 parts of filler, 1-5 parts of organic titanium catalyst, 1-3 parts of aminosilane coupling agent, 50-150 parts of vinyl silicone oil, 0.1-0.5 parts of peroxide. This scheme uses vinyl silicone oil and peroxide to retain the original heat resistance and high temperature to enable the silicone sealant to be deeply cured, while the mechanical properties are greatly improved. The silicone sealant prepared by this scheme has the advantages of single component, high temperature resistance, low cost, and is suitable for U-shaped heating tubes and other parts with high requirements for deep curing and temperature resistance, and can be widely used;

[0007] Further observation of paragraph 11 of the description of this scheme shows that, although this scheme also discloses the use of an organic metal compound, the organic metal compound used in this scheme is an organic titanium compound, and its main function is to be used as a catalyst.

[0008] The problem to be solved by this scheme is: how to provide a formula of a one-component sealant that is resistant to high temperatures and UV radiation. Summary of the invention

[0009] The object of the present invention is to provide a formula of a one-component sealant having high temperature resistance and UV resistance;

[0010] Another object of the present application is to provide a method for preparing the above-mentioned one-component sealant.

[0011] To achieve the above object, the present application discloses a one-component sealant, which comprises the following components by weight:

[0012]

[0013] The organic metal compound is selected from at least one of tris(triphenylphosphine)copper fluoride, tris(triphenylphosphine)copper chloride, tris(triphenylphosphine)copper bromide, bis(triphenylphosphine)nickel difluoride, bis(triphenylphosphine)nickel dichloride and bis(triphenylphosphine)nickel dibromide.

[0014] Preferably, the following components are included by weight:

[0015]

[0016] Preferably, the crosslinking agent is selected from at least one of vinyltributylacetoximosilane, methyltributylacetoximosilane, tetrabutylketoneximosilane, phenyltributylacetoximosilane and vinyltris(methylisobutylketoneximo)silane.

[0017] Preferably, the organometallic compound is a mixture of tri(triphenylphosphine)copper chloride and bis(triphenylphosphine)nickel dichloride, and the mass ratio of tri(triphenylphosphine)copper chloride to bis(triphenylphosphine)nickel dichloride is 1:0.5-0.8.

[0018] Preferably, the crosslinking agent is selected from tetrabutyl ketone oxime silane, phenyl tributyketone oxime silane, and vinyl tris (methyl isobutyl ketone oxime) silane, and the mass ratio of tetrabutyl ketone oxime silane, phenyl tributyketone oxime silane, and vinyl tris (methyl isobutyl ketone oxime) silane is 2 to 4:1:1.

[0019] Preferably, the catalyst is selected from at least one of dibutyltin dilaurate, dibutyltin diacetate, dioctyltin dilaurate, dibutyltin didodecylsulfide, stannous octoate, and tin dibutylacetylacetonate.

[0020] Preferably, the dewatering agent is selected from at least one of isocyanate siloxane, vinyl trimethoxy silane and vinyl triethoxy silane;

[0021] The α,ω-dihydroxy polysiloxane includes high-viscosity α,ω-dihydroxy polysiloxane and low-viscosity α,ω-dihydroxy polysiloxane;

[0022] The viscosity of the high-viscosity α,ω-dihydroxy polysiloxane is 80000-100000 mPa·s;

[0023] The viscosity of the low-viscosity α,ω-dihydroxy polysiloxane is 5000 to 20000 mPa·s;

[0024] The mass ratio of the high-viscosity α,ω-dihydroxy polysiloxane to the low-viscosity α,ω-dihydroxy polysiloxane is 2-4:1.

[0025] Preferably, the shear strength attenuation rate of the one-component sealant after 1700 hours of salt spray, ultraviolet irradiation, high and low temperature tests is no more than 7%.

[0026] In addition, the present application also discloses a method for preparing the above-mentioned one-component sealant, comprising the following steps:

[0027] Step 1: mixing α,ω-dihydroxy polysiloxane, hydrophobic fumed silica, nano calcium carbonate, silicon micropowder, carbon black and a dehydrating agent, and heating to obtain an intermediate;

[0028] Step 2: Mix the intermediate obtained in step 1 with a cross-linking agent, a catalyst, and an organic metal compound to obtain a single-component sealant.

[0029] Preferably, in step 1, high viscosity α, ω-dihydroxy polysiloxane, low viscosity α, ω-dihydroxy polysiloxane, hydrophobic fumed silica, nano calcium carbonate, silicon micropowder, carbon black and a dehydrating agent are mixed and heated to a temperature of 130 to 140° C. and dehydrated to obtain an intermediate material.

[0030] The beneficial effects of this application are:

[0031] The present application improves the anti-ultraviolet performance and high and low temperature stability of the single-component sealant to a certain extent by adding organic metal compounds such as tri(triphenylphosphine) copper fluoride, and the initial shear strength of the single-component sealant after drying also has a certain degree of upward trend with the addition of tri(triphenylphosphine) copper fluoride. We believe that the reason for the above phenomenon may be that during the cross-linking process, the copper ions in tri(triphenylphosphine) copper fluoride are activated by coordination, which may more effectively promote the cross-linking reaction and thus form a three-dimensional network between the molecular chains of the sealant, thereby enhancing the internal structure of the material. This network structure can provide higher tensile strength, tear strength and wear resistance, making the sealant less likely to break or deform when subjected to external forces; at the same time, the cross-linked sealant has a stronger resistance to chemicals and environmental factors (such as moisture, oxygen, ultraviolet rays, etc.). The cross-linked structure reduces the mobility of the molecular chain and reduces the possibility of chemical erosion and oxidative degradation. DETAILED DESCRIPTION

[0032] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. In the description of the present invention, it should be noted that, if no specific conditions are specified in the embodiments, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0033] A method for preparing a one-component sealant comprises the following steps:

[0034] Step 1: mixing high viscosity α, ω-dihydroxy polysiloxane, low viscosity α, ω-dihydroxy polysiloxane, hydrophobic fumed silica, nano calcium carbonate, silicon powder, carbon black, and a dehydrating agent, and heating to a temperature of 130 to 140° C., heating and dehydrating to obtain an intermediate material;

[0035] Step 2: Mix the intermediate obtained in step 1 with a cross-linking agent, a catalyst, and an organic metal compound to obtain a single-component sealant.

[0036] The viscosity of the high-viscosity α,ω-dihydroxy polysiloxane is 80000 mPa·s;

[0037] The viscosity of the low-viscosity α,ω-dihydroxy polysiloxane is 10000 mPa·s;

[0038] The mass ratio of the high viscosity α, ω-dihydroxy polysiloxane to the low viscosity α, ω-dihydroxy polysiloxane is 3:1

[0039] Examples 1-4

[0040] A one-component sealant, the formula is shown in Table 1:

[0041] Table 1

[0042]

[0043] Example 5

[0044] The method is basically the same as Example 1, except that a mixture of phenyltributylacetonato silane and vinyltri(methylisobutylketone oxime)silane of the same mass is used to replace tetrabutylketone oxime silane, and the mass ratio of phenyltributylacetonato silane to vinyltri(methylisobutylketone oxime)silane is 2:1.

[0045] Example 6

[0046] The method is basically the same as Example 1, except that a mixture of tetrabutyl ketone oxime silane and phenyltributyketone oxime silane with the same total mass is used to replace tetrabutyl ketone oxime silane, and the mass ratio of tetrabutyl ketone oxime silane to phenyltributyketone oxime silane is 2:1.

[0047] Example 7

[0048] The method is basically the same as Example 1, except that a mixture of tetrabutyl ketone oxime silane and vinyl tris (methyl isobutyl ketone oxime) silane with the same total mass is used instead of tetrabutyl ketone oxime silane, and the mass ratio of tetrabutyl ketone oxime silane to vinyl tris (methyl isobutyl ketone oxime) silane is 2:1.

[0049] Example 8

[0050] The method is basically the same as Example 1, except that a mixture of tetrabutyl ketone oxime silane, phenyl tributyketone oxime silane and vinyl tris (methyl isobutyl ketone oxime) silane with the same total mass is used instead of tetrabutyl ketone oxime silane, and the mass ratio of tetrabutyl ketone oxime silane, phenyl tributyketone oxime silane and vinyl tris (methyl isobutyl ketone oxime) silane is 2:1:1.

[0051] Example 9

[0052] The method is substantially the same as Example 1, except that the same mass of bis(triphenylphosphine)nickel dichloride is used instead of tri(triphenylphosphine)copper chloride.

[0053] Example 10

[0054] The method is basically the same as Example 1, except that a mixture of tri(triphenylphosphine) copper chloride and bis(triphenylphosphine) nickel dichloride with the same total mass is used instead of tri(triphenylphosphine) copper chloride, and the mass ratio of tri(triphenylphosphine) copper chloride to bis(triphenylphosphine) nickel dichloride is 1:0.6.

[0055] Embodiment 11

[0056] The method is basically the same as Example 8, except that a mixture of tri(triphenylphosphine) copper chloride and bis(triphenylphosphine) nickel dichloride with the same total mass is used instead of tri(triphenylphosphine) copper chloride, and the mass ratio of tri(triphenylphosphine) copper chloride to bis(triphenylphosphine) nickel dichloride is 1:0.6.

[0057] Example 12

[0058] The method is substantially the same as Example 1, except that dibutyltin diacetate is used instead of dibutyltin dilaurate.

[0059] Embodiment 13

[0060] The method is substantially the same as Example 1, except that the α,ω-dihydroxy polysiloxane is a high-viscosity α,ω-dihydroxy polysiloxane having a viscosity of 80,000 to 100,000 mPa·s.

[0061] Embodiment 14

[0062] The method is substantially the same as Example 1, except that the α,ω-dihydroxy polysiloxane is a low-viscosity α,ω-dihydroxy polysiloxane having a viscosity of 5000 to 20000 mPa·s.

[0063] Comparative Examples 1-4

[0064] A sealant, the formula of which is shown in Table 2:

[0065] Table 2

[0066]

[0067]

[0068] Performance Test:

[0069] The test results are shown in Table 3:

[0070]

[0071]

[0072] Result analysis:

[0073] 1. It can be seen from Examples 1-4 that, although the initial shear strengths of the various examples are slightly different after adjusting the addition amounts of the various components in the formula, the shear strength attenuation rates after 1700h of salt spray, ultraviolet irradiation, and high and low temperature tests show a certain gap, which shows that Example 1 is the best formula;

[0074] 2. It can be seen from Examples 1 and 5-7 that when a mixture of any two of tetrabutyl ketoxime silane, vinyl tris (methyl isobutyl ketoxime) silane and phenyl tris (butyl ketoxime silane) is used to replace tetrabutyl ketoxime silane, the initial shear strength of the sealant and the shear strength attenuation rate after 1700h salt spray, ultraviolet irradiation, high and low temperature test, the change rate of tensile strength after aging, and the change rate of elongation after aging do not show obvious change trends. Even the initial shear strength of Examples 5-7 shows a certain degree of downward trend, and the change rate of tensile strength shows a certain upward trend;

[0075] When the mixture of tetrabutyl ketoxime silane, vinyl tris (methyl isobutyl ketoxime) silane and phenyl tris (methyl isobutyl ketoxime) silane in Example 8 replaced tetrabutyl ketoxime silane, the initial shear strength of the sealant was significantly improved. At the same time, the shear strength attenuation rate of the material coating was significantly reduced after 1700h of salt spray, ultraviolet irradiation, and high and low temperature tests. The change rate of tensile strength and the change rate of elongation at break after aging were closer to 0. It can be seen that when tetrabutyl ketoxime silane, vinyl tris (methyl isobutyl ketoxime) silane and phenyl tris (methyl isobutyl ketoxime) silane are used in combination, a multiple cross-linked network is formed, which enhances the internal structure of the sealant and improves its thermal stability. In addition, there may be a synergistic effect between different cross-linking agents, which may be due to the interaction between the cross-linking agents, such as the complementarity of the cross-linking points, thereby improving the overall performance of the sealant.

[0076] 3. It can be seen from Examples 1 and 10-11 that when the organic metal compound is used alone, the initial shear strength of the sealant is improved to a certain extent and the attenuation rate is suppressed to a certain extent;

[0077] When the cross-linking agent and the organic metal are compounded at the same time, the initial shear strength of the sealant is significantly improved and the attenuation rate is significantly suppressed. In combination with the data of Example 8, it can be seen that the improvement trend of the above two properties far exceeds the performance improvement effect achieved by the simple superposition of Example 8 and Example 10. Therefore, we believe that when the cross-linking agent and the organic metal are compounded at the same time, a synergistic effect is generated between the organic metal and the cross-linking agent, which leads to the unexpected improvement of the shear strength of Example 11 and the unexpected suppression of the attenuation rate;

[0078] 4. It can be seen from Examples 1 and 13-14 that when using high-viscosity α, ω-dihydroxy polysiloxane or low-viscosity α, ω-dihydroxy polysiloxane alone, although Examples 13 and 14 are improved in some aspects relative to Example 1, such as Example 13 having a faster drying time, overall, Examples 13 and 14 have weak positive improvement capabilities for sealant performance, showing an effect that disadvantages outweigh advantages. Therefore, this application does not recommend using high-viscosity α, ω-dihydroxy polysiloxane or low-viscosity α, ω-dihydroxy polysiloxane alone;

[0079] 5. It can be seen from Example 1 and Comparative Examples 1-4 that when the amount of organic metal compound added is too large or too small, the attenuation rate of the sealant shows a significant upward trend. We believe that the reason for this phenomenon may be that as the amount of organic metal compound added changes, the sealant is over-crosslinked and too many cross-linking points are formed, which makes the sealant brittle and hard, and loses its due elasticity and flexibility. When the amount of organic metal compound added is too small, it may not provide enough cross-linking points, resulting in insufficient cross-linking density of the sealant, thereby affecting its mechanical strength and durability. At the same time, it can be seen from Comparative Examples 2-3 that after the organic metal compound is replaced by metal oxide or peroxide in the present application, the attenuation rate of the sealant also shows a significant upward trend. It can be seen that the metal compound in the present application is difficult to replace.

Claims

1. A one-component sealant, characterized in that: By mass, it includes the following components: 43 parts of α,ω-dihydroxypolysiloxane; 8 parts of hydrophobic fumed silica; 46 parts of nano calcium carbonate; Silica powder 6 parts; 0.8 parts of carbon black; 1.5 parts of dewatering agent; 10 parts of cross-linking agent; 0.05 parts of catalyst; 0.4 parts of organometallic compound; The organometallic compound is a mixture of tri(triphenylphosphine)copper chloride and bis(triphenylphosphine)nickel dichloride, and the mass ratio of tri(triphenylphosphine)copper chloride to bis(triphenylphosphine)nickel dichloride is 1:0.6; The crosslinking agent is a mixture of tetrabutyl ketone oxime silane, phenyl tributyketone oxime silane and vinyl tris (methyl isobutyl ketone oxime) silane, and the mass ratio of tetrabutyl ketone oxime silane, phenyl tributyketone oxime silane and vinyl tris (methyl isobutyl ketone oxime) silane is 2:1:

1.

2. The one-component sealant according to claim 1, characterized in that: The catalyst is selected from at least one of dibutyltin dilaurate, dibutyltin diacetate, dioctyltin dilaurate, dibutyltin didodecylsulfide, stannous octoate and tin dibutylacetylacetonate.

3. The one-component sealant according to claim 1, characterized in that: The dewatering agent is selected from at least one of isocyanate siloxane, vinyl trimethoxy silane and vinyl triethoxy silane; The α,ω-dihydroxy polysiloxane includes high-viscosity α,ω-dihydroxy polysiloxane and low-viscosity α,ω-dihydroxy polysiloxane; The viscosity of the high-viscosity α,ω-dihydroxy polysiloxane is 80000-100000 mPa·s; The viscosity of the low-viscosity α,ω-dihydroxy polysiloxane is 5000 to 20000 mPa·s; The mass ratio of the high-viscosity α,ω-dihydroxy polysiloxane to the low-viscosity α,ω-dihydroxy polysiloxane is 2-4:

1.

4. The one-component sealant according to claim 1, characterized in that: The shear strength attenuation rate of the one-component sealant after 1700 hours of salt spray, ultraviolet irradiation, high and low temperature tests is no more than 5%.

5. A method for preparing the one-component sealant according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: mixing α,ω-dihydroxy polysiloxane, hydrophobic fumed silica, nano calcium carbonate, silicon micropowder, carbon black and a dehydrating agent, and heating to obtain an intermediate; Step 2: Mix the intermediate obtained in step 1 with a cross-linking agent, a catalyst, and an organic metal compound to obtain a single-component sealant.

6. The method for preparing a one-component sealant according to claim 5, characterized in that: In the step 1, high viscosity α, ω-dihydroxy polysiloxane, low viscosity α, ω-dihydroxy polysiloxane, hydrophobic fumed silica, nano calcium carbonate, silicon powder, carbon black, and a dehydrating agent are mixed and heated to a temperature of 130 to 140° C. to dehydrate and obtain an intermediate material.

Citation Information

Patent Citations

  • Organic silicon sealant for U-shaped heating pipe and preparation method thereof

    CN113956835A

  • A high-temperature resistant sealant, its preparation method, and its application.

    CN114085644B

  • Single-component silicone sealant and preparation method thereof

    CN109694686A

  • High-viscosity and high-temperature-resistant dimer acid type polyamide hot melt adhesive and preparation method thereof

    CN116731662A